Interpretation of the Meaning of the Term Islam in Al-ManÄr Tafsir and Its Relationship to Inter-Religious and Inter-Cultural Relations - Saifullah, Saifullah (Dialogia, 2023)
This article examines the interpretations of “al-IslÄm” and its effects on inter-religious and intercultural relationships. It focuses on al-Manar's interpretation of the terms "al-IslÄm" in the Qur'an Ali Imran 19 and 85. The research method used is a qualitative content analysis and contextual approach to al-Qur’an interpretation. The findings show that interpreting "al-islÄm" in the al-ManÄr commentary differs from other tafsir works and emphasizes the importance of internal reflection and improvement for the Muslim community. The study highlights the complexity of Islam and its various interpretations and how it can affect relationships and attitudes towards different religious and cultural groups. The study provides a unique contribution to Islamic studies by exploring the interpretation of keywords in the Quran and its impact on inter-religious and intercultural relationships.